Pengoptimalan Fungsi Magnetik dan Sistem Hidrolik pada Alat Penyangga Mesin Mobil dalam Menerapkan Budaya K3 di Dunia Industri Otomotif - Kristanto, Zanuri; Yogatama, Muhamad Andito; Widyawati, Linda; Dewi, Alyna Kirana; Lathifah, Fauziyah Nur; Wijayanto, Danar Susilo (FKIP Universitas Sebelas Maret, 2024)
Speed and accuracy of workmanship are important supporting factors for business actors operating in the service sector. The availability of adequate supporting equipment can increase work productivity and can reduce the risk of work accidents that can endanger the surrounding environment. Technological developments in the automotive industry always provide innovations. Even though it is like that, it still doesn't escape the new problems that accompany it. In the process of replacing a car clutch lining, the application of knowledge about lifting aircraft is very necessary. Differences in the load capacity of car engines that exceed human strength capacity require the use of tools according to specifications. The addition of a hydraulic system to the machine support can provide lifting power that is greater than the power produced by mechanics in lifting or holding loads that exceed their capacity. Apart from that, implementing a culture of occupational health and safety is important to realize workforce welfare. What is not expected when repairing a car's clutch lining is a shift in the load support of the car's engine which can cause damage to other components and can even endanger mechanical safety. The property of magnets that can attract metal objects can be used to improve K3 in the automotive industry as an effort to prevent engine supports from shifting position when repairs are carried out on car clutch linings.